Landscape - Sijmons, Dirk. (Amsterdam : Architectura And Natura Dist, 2002)
Landscape is one of the few Dutch words that has found its way into other languages. The debate on the future of the Dutch man-made landscape, its valuable heritage and the transfomations of the present landscape is the main theme of =Landscape . Even today attractive , living man-made landscapes are still being created. New assignments ranging from the extraction of drinking water to cultivation under glass and from sub-urbanisation to wind turbines are points on the programme for designing the landscape of the twenty-first century. The plans in this book offer a glimpse of this. With this publication, the Dutch office H+N+S landcapes architects wants to emphasise the task of regaining the pleasure of creating our landscape that cultural policy makers have: the Netherlands should once again be regarded as a work of art!
Keywords: Landscape architecture -- Netherlands; Land use--Planning